Strategi Pengembangan Destinasi Wisata Hutan Bambu Zona 2 Bekasi - Emersiana Putri Talo; Dyah Mustika Wardhani; Gilang Fahreza (Tamasya : Jurnal Pariwisata Indonesia, 2026)
Tourism plays an important role in regional development, requiring sustainable strategies to improve destination management. Hutan Bambu Zona 2 Bekasi is a natural tourism destination with considerable potential but still faces challenges related to facilities, environmental cleanliness, and destination management. This study aims to analyze the destination based on the components of Attraction, Accessibility, Amenities, and Ancillary Services (4A) and to provide recommendations for destination development. This study employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The results indicate that Hutan Bambu Zona 2 Bekasi has strong natural Attractions, relatively good Accessibility, and adequate supporting services. However, several issues remain, including limited facilities, suboptimal river cleanliness, and insufficient visitor information. The recommended development efforts focus on improving tourism facilities, strengthening digital promotion, enhancing stakeholder collaboration, and implementing sustainable environmental management. The findings are expected to support destination managers and local governments in improving the quality, competitiveness, and sustainability of Hutan Bambu Zona 2 Bekasi.